Social meaning as an innovation for image building in academic institutions such as the University of the Philippines Mindanao - Babiera, Kent John M.; Escano, Ma. Teresa R. (2018)
Most academic institution have been focusing on producing graduates which can be globally competitive so much so that they often forget to also develop their immediate community which resulted to weaker public relationship. Hence, this study explored using the concept of Social Meaning in strengthening relationship of the public and the academic institution. Social meaning is the intangible aspects of the academe that the public perceive as important and integral because of the long-term benefits to them individually and to the community they are residing. University of the Philippines Mindanao was used as a case in point of the study. As a stated in the mission statement of the university, it aims to provide affordable quality education and serve the region. The study interpreted this statement in relation to the public?s perception of quality education and developed a social meaning that UP Mindanao sensibly nurture students to develop themselves and their community, for them to lead and be part in the nation-building and socio-economic development of the country. In order to communicate the developed social meaning, an Integrated Marketing Communications (IMC) plan was developed with various strategies, special events, and tactics in New Media, Advertising, and Public Relations to secure that the message would be communicated efficiently. The study also used Diffusion of Innovation Theory?s five-step diffusion process as a guide in crafting the different programs and executions in the IMC Plan.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2018